Longterm remission of left posterior fascicular ventricular tachycardia due to mechanical trauma - Parizek, Petr; Popelka, Jiri; Haman, Ludek (Revista médica de Chile, 2010)
We present a case of a 28 year old woman with paroxysmal left posterior fascicular ventricular tachycardia (LPFVT). Ventricular tachycardia was not inducible after completing of left ventricle 3D reconstruction. Even though catheter ablation was not performed, no LPFVT recurrence has been documented during 60 months follow-up. We surmise that we caused mechanical trauma during the mapping of the posterior fascicle that damaged arrhythmogenic structures and subsequently led to long term remission of the left posterior fascicular ventricular tachycardia.
Keywords: časové faktory; Bundle-Branch Block; srdeční komory; Time Factors; Heart Ventricles; Adult; dospělí; blokáda Tawarova raménka; katetrizační ablace; ženské pohlaví; lidé; Catheter Ablation; indukce remise; Female; komorová tachykardie; Tachycardia, Ventricular; Humans; Remission Induction